Four Years of Continuous Seafloor Displacement Measurements in the Campi Flegrei Caldera - De Martino, Prospero; Guardato, Sergio; Donnarumma, Gian Paolo; Dolce, Mario; Trombetti, Tiziana; Chierici, Francesco; Macedonio, Giovanni; Beranzoli, Laura; Iannaccone, Giovanni (Frontiers in Earth Science, 2020)
We present four years of continuous seafloor deformation measurements carried out in the Campi Flegrei caldera (Southern Italy), one of the most hazardous and populated volcanic areas in the world. The seafloor sector of the Caldera has been monitored since early 2016 by the MEDUSA marine research infrastructure, consisting of four instrumented buoys installed where sea depth is less than 100 m. Each MEDUSA buoy is equipped with a cabled, seafloor module with geophysical and oceanographic sensors and a subaerial GPS station providing seafloor deformation and other environmental measures. Since April 2016, the GPS vertical displacements at the four buoys show a continuous uplift of the seafloor with cumulative measured uplift ranging between 8 cm and 20 cm. Despite the data being affected by environmental noise associated with sea and meteorological conditions, the horizontal GPS displacements on the buoys show a trend coherent with a radial deformation pattern. We use jointly the GPS horizontal and vertical velocities of seafloor and on-land deformations for modeling the volcanic source, finding that a spherical source fits best the GPS data. The geodetic data produced by MEDUSA has now been integrated with the data flow of other monitoring networks deployed on land at Campi Flegrei.